Characterising the invertebrate megafaunal assemblages of a deep-sea (200–3000 m) frontier region for oil and gas exploration: the Great Australian Bight, Australia. (November 2018) - Williams, Alan; Althaus, Franziska; MacIntosh, Hugh; Loo, Maylene; Gowlett-Holmes, Karen; Tanner, Jason E.; Sorokin, Shirley J.; Green, Mark
Abstract: The first systematic benthic survey in the deep sea (200–3000 m) of Australia's Great Australian Bight (GAB) was undertaken in 2015 to characterise the invertebrate megafauna, and to inform the selection of indicators and metrics for ecological monitoring ahead of oil and gas exploration. The survey yielded more than 629 species of invertebrate megafauna; of the 376 species with distributional data, 92 (25%) were undescribed and 77 were new records for Australian waters. The families and genera present were all known to occur in the deep sea and many species had been previously recorded in Australia and worldwide; faunal composition was broadly typical for temperate deep-sea regions. The highest diversities (>80 putative species, or Operational Taxonomic Units, OTUs) were recorded within the higher taxa Demospongiae, Decapoda, Gastropoda and Echinodermata. Multispecies analyses showed clear changes in the assemblage structure with depth; sponges and echinoderms dominated the overall biomass and density, with the former being more prominent in shallower depths. The assemblage structure is consistent with the GAB being a single provincial-scale bioregion, with no longitudinal pattern in assemblage, biomass or density distribution. Approximately 70% of species that could be assigned biogeographic data were previously recorded from Australia, with less than half (146 species, 39%) previously known from the GAB. Only two described species, the crab Choniognathus granulosus and barnacle Arcoscalpellum inum, appear restricted to the GAB; it would be premature to assign any undescribed species as having endemic status. The clear eastwards biogeographic affinity of the GAB fauna is influenced by the relatively high deep-sea sampling effort to the east off southeastern Australia and New Zealand. Our survey of invertebrate megafauna at baseline (unperturbed) sites provides the basis to evaluate indicators and metrics using a reference-site monitoring approach. A robust (consistent species-level) taxonomic foundation will enable a variety of assemblage-level (composite) metrics (e.g. richness, diversity, distinctness) to be derived, and this is possible across several major taxa including Porifera, Cnidaria, Mollusca, Echinodermata and Crustacea. Species-level data also permit structural and functional changes (including recovery) to be assessed in response to disturbance. Where reference sites should be established can only be determined once the exploration phase of industry development is further advanced because the spatial scales of potential impact are highly activity-specific. However, our data show the high importance of depth to selecting monitoring sites because invertebrate megafaunal assemblage composition (turnover), diversity, and abundance are all highly correlated with depth. Conversely, latitude is not important because the central GAB is a single biogeographic province.